Financial sustainability of the right to free primary education in Nigeria: what we know and what we need to do? (2017)
This paper explored the development of free primary education in Nigeria and analysed the barriers to its effective implementation and continuous sustenance over the years. This was done by examining the country’s legislations in comparison to its obligations under relevant international human rights instruments. As analysed, Nigeria has not effectively implemented free primary education as required by relevant international instruments to which it is a State party and it has essentially failed to undertake the required measures in order to fully eliminate the payment of fees in primary schools within its public educational system. In this paper, it will be noted that Nigeria has made attempts at implementing the right to free primary education for all children albeit there are still several challenges being encountered. This is further justified by the evidence that costs of schooling are considered a reason for school dropout. Nigeria would appear to be complying with international standards based on the inclusion of the provision of free, compulsory primary education presently in its domestic laws such as the Convention on the Rights of the Child (CRA) and the Compulsory Free Universal Basic Education Act (UBE Act). Both legislations do make an affirmative obligation to a positive right to free and compulsory education. However, besides these positive legislative aspects, according to the international standards, Nigeria appears to be non-compliant in several important practical ways. A central challenge is the lack of a substantive provision guaranteeing the right to free and compulsory primary education in the Nigerian constitution, which is the ‘grundnorm ’. The Constitution does not expressly provide for a substantive right to education, rather, it only provides the legal framework for educational objectives and management in the country